Identification of iron metabolism-related genes in coronary heart disease and construction of a diagnostic model - Zhu, Lin; Zhang, Jianxin; Fan, Wenhui; Su, Chen; Jin, Zhi (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCoronary heart disease is a common cardiovascular disease, yferroptosiset its relationship with iron metabolism remains unclear.MethodsGene expression data from peripheral blood samples of patients with coronary heart disease and a healthy control group were utilized for a comprehensive analysis that included differential expression analysis, weighted gene co-expression network analysis, gene enrichment analysis, and the development of a logistic regression model to investigate the associations and differences between the groups. Additionally, the CIBERSORT algorithm was employed to examine the composition of immune cell types within the samples.ResultsEight central genes were identified as being both differentially expressed and related to iron metabolism. These central genes are mainly involved in the cellular stress response. A logistic regression model based on the central genes achieved an AUC of 0.64–0.65 in the diagnosis of coronary heart disease. A higher proportion of M0 macrophages was found in patients with coronary heart disease, while a higher proportion of CD8T cells was observed in the normal control group.ConclusionThe study identified important genes related to iron metabolism in the pathogenesis of coronary heart disease and constructed a robust diagnostic model. The results suggest that iron metabolism and immune cells may play a significant role in the development of coronary heart disease, providing a basis for further research.